2018
DOI: 10.3928/1081597x-20180726-01
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Unplanned Vitrectomies in Femtosecond Laser–Assisted Cataract Surgery Compared to Conventional Phacoemulsification

Abstract: FLACS had a rate of unplanned vitrectomy comparable to conventional phacoemulsification. There was no statistically significant difference in unplanned vitrectomy rates between early and late FLACS cases suggesting a short learning curve. [J Refract Surg. 2018;34(9):610-614.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Several studies reporting collectively on nearly 1.3 million cataract surgeries have found rates of posterior capsular tear or vitreous loss ranging from 0.19% to 6.7%. 9,11,20–41 As such, the rate of unplanned vitrectomy reported in this study is similar to or lower than that reported in the literature. Likewise, the incidence of retinal complications for which the patient had to be referred to a retina surgeon (0.072%) was also lower than the literature-reported incidence of retinal detachment/retinal tear (0.18% to 1.4%).…”
Section: Discussionsupporting
confidence: 85%
“…Several studies reporting collectively on nearly 1.3 million cataract surgeries have found rates of posterior capsular tear or vitreous loss ranging from 0.19% to 6.7%. 9,11,20–41 As such, the rate of unplanned vitrectomy reported in this study is similar to or lower than that reported in the literature. Likewise, the incidence of retinal complications for which the patient had to be referred to a retina surgeon (0.072%) was also lower than the literature-reported incidence of retinal detachment/retinal tear (0.18% to 1.4%).…”
Section: Discussionsupporting
confidence: 85%
“…10,41,97 Either way, the overall implications of all capsule-related complications (such as the need for vitreoretinal or affecting visual outcomes) seem to be not statistically significant in a global comparison between FLACS and CP. 40,79,98 Nevertheless, the impact of such events should not be underestimated in the context of premium IOL implantation, as it irrevocably compromises surgical success, as capsular integrity and further optimal centration are paramount in the final result. Unfortunately, literature comparing low-energy FLACS and CP that contemplates this niche or subgroup of refractive cataract surgery is scarce, although not absent.…”
Section: Complicationsmentioning
confidence: 99%